2010
DOI: 10.4103/0970-4388.76159
|View full text |Cite
|
Sign up to set email alerts
|

Mother′s knowledge about pre-school child′s oral health

Abstract: Children under the age of 5 years generally spend most of their time with their parents and guardians, especially mothers, even when they attend pre-schools or nurseries. It has been found that young children's oral health maintenance and outcomes are influenced by their parent's knowledge and beliefs. This study was done to assess the mother's knowledge about the oral health of their pre-school children in Moradabad, India. Mothers of children aged 1-4 years, attending the hospital for vaccination or regular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
31
6
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 1 publication
8
31
6
2
Order By: Relevance
“…Despite of that, children's mothers without CPI showed to have a greater knowledge than children's mothers with CPI. Similar result was found in a study in which the majority of mothers (73.9%) showed a good knowledge of the diet of their children [9].…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…Despite of that, children's mothers without CPI showed to have a greater knowledge than children's mothers with CPI. Similar result was found in a study in which the majority of mothers (73.9%) showed a good knowledge of the diet of their children [9].…”
Section: Discussionsupporting
confidence: 76%
“…This fact can be explained by the knowledge of parents about the determinants of dental caries not being sufficient stimulus for the adoption of care with the children's oral health, reinforcing the idea that there is not necessarily a causal relationship between information and action [18]. Contrary to the findings of the present study, other authors found that the majority of the population studied presented a partial knowledge about care with oral hygiene [9] and classified as a limited knowledge regarding the habits of oral hygiene of parents evaluated, especially in relation to the form of realization of brushing and importance of consultation for the prevention [21].…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations